Performance Evaluation of a Community-Scale Fiberglass Anaerobic Digester for Biogas and Nutrient Recovery - Rahmat Sabani; Ari Handono Ramelan; Pranoto Pranoto; Mohammad Masykuri (Advance Sustainable Science Engineering and Technology, 2026)
The management of organic waste using an anaerobic reactor offers the potential for renewable energy production and nutrient recovery. This study evaluates the performance of a 3,000 L fiberglass anaerobic reactor designed to treat a mixture of kitchen waste, cow manure, and water in a 1:1:1 ratio. The process was conducted under mesophilic conditions (30–38 °C) over a 40-day batch cycle. The reactor produced a total of 63.75 m³ of biogas with an average methane content of 59.3%, equivalent to 0.193 m³ CH₄/kg VS. Additionally, the system produces approximately 2,700 kg/month of liquid effluent and 900 kg/month of stabilized solids. These results demonstrate the efficiency of substrate bioconversion and the potential for utilizing residues as organic fertilizer. This study emphasizes the technical feasibility of using a community-scale fiberglass reactor for organic waste treatment with measurable performance parameters.